Cutinase and non-specific esterase activities in the conidial mucilage of Colletotrichum graminicola - Pascholati, S. F. [UNESP]; Deising, H.; Leiti, B.; Anderson, D.; Nicholson, R. L. (Elsevier, 1993)
Colletotrichum graminicola is the causal agent of anthracnose on a variety of graminaceous monocotyledonous plants, including corn and sorghum. When conidia of C. graminicola are produced in acervuli on infected plant tissues or in culture, they are surrounded by a mucilage. The mucilage, which is composed of high molecular weight glycoproteins, various enzymes, and a self-inhibitor of conidium germination, functions to protect condidia from untimely germination, from desiccation, and from toxic phenolic metabolites produced by the host plant in response to infection. The present investigation demonstrates that the mucilage contains four cutinases whose molecular weights are similar to those of other fungal cutinases. Like other cutinases these enzymes are of the serine-esterase class of hydrolases as shown by inhibition of enzyme activity with diisopropyl fluorophosphate (DIPF). In the presence of high concentrations of DIPF, conidia produced apparently normal, mature appressoria yet were unable to cause disease of corn leaves. The function of the mucilage cutinases is discussed with regard to their importance to the infection process. © 1993 Academic Press, Inc.
Keywords: DIPF, diisopropyl fluorophosphate; DPM, disintegrations per minute